2013
DOI: 10.1093/gbe/evt067
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Cis-Regulatory Changes Involved in the Evolution of Aerobic Fermentation in Yeasts

Abstract: Gene regulation change has long been recognized as an important mechanism for phenotypic evolution. We used the evolution of yeast aerobic fermentation as a model to explore how gene regulation has evolved and how this process has contributed to phenotypic evolution and adaptation. Most eukaryotes fully oxidize glucose to CO2 and H2O in mitochondria to maximize energy yield, whereas some yeasts, such as Saccharomyces cerevisiae and its relatives, predominantly ferment glucose into ethanol even in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The effect of A35 on the binding of top2α to DNA was evaluated using an electrophoretic mobility shift (EMSA) kit (Invitrogen) as previously described [ 60 ] according to the manufacturer's protocol. Oligonucleotides containing a strong top2 binding site corresponding to residues 87–126 of the pBR322 plasmid were annealed, and 1 nm was incubated with nuclear extracts (5 μg) from K562 cells in reaction buffer (750 mM KCl, 0.5 mM dithiothreitol, 0.5 mM EDTA, 50 mM Tris, pH 7.4) on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of A35 on the binding of top2α to DNA was evaluated using an electrophoretic mobility shift (EMSA) kit (Invitrogen) as previously described [ 60 ] according to the manufacturer's protocol. Oligonucleotides containing a strong top2 binding site corresponding to residues 87–126 of the pBR322 plasmid were annealed, and 1 nm was incubated with nuclear extracts (5 μg) from K562 cells in reaction buffer (750 mM KCl, 0.5 mM dithiothreitol, 0.5 mM EDTA, 50 mM Tris, pH 7.4) on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, physiological and metabolic traits have frequently evolved through changes in both protein-coding and cis-regulatory regions ( Ihmels et al. 2005 ; Lin et al. 2013 ; Roop et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the specific evolutionary patterns of TFs ( Coulombe-Huntington and Xia 2012 ) and of promoter sequences and TFBSs in the yeast genome ( Doniger and Fay 2007 ; Tirosh et al 2008 ; Tirosh, Barkai, et al 2009 ; Chen et al 2010 ; Tsai et al 2012 ; Lin et al 2013 ). A recent study found that regulatory motif variation is associated with gene expression differences between S. cerevisiae strains ( Connelly et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%